In-plane shear behaviour of stone masonry piers: A numerical study - Araújo, Ana S. (2014)
Post-earthquake investigations have shown that if out-of-plane mechanisms are prevented, the seismic performance of a masonry building depends mainly on the in- plane capacity of spandrels beams and especially piers. For this reason, several investigations were done in the past to characterize the in-plane behaviour of masonry walls. A large majority of these studies consist of experimental programmes, testing the lateral response of piers. Nevertheless, very few studies focused on carrying out numerical studies and their potential was disregarded. A numerical investigation to study the in-plane behaviour of masonry piers was carried out, based on an experimental campaign performed on stone masonry piers. The experimental programme included masonry piers with two slenderness ratios subjected to two distinct levels of axial compression. Finite element models were built on the advanced software, DIANA, and according to the experimental setup test of each wall, with the aim of simulating the experimental tests. Afterwards, the non-linear numerical simulations were compared against the in-plane cyclic test results. The calibration and validation of the numerical models according to the experimental results was conducted. The results of the non-linear analyses carried out on the validated models are presented and discussed. Good agreement between experimental and numerical results was achieved both considering the force- displacement behaviour and failure mechanisms. The numerical strategy can be seen as a complementary way to study masonry piers, particularly useful for further parametrical studies.